Environmental arts therapy the wild frontiers of the heart - Heginworth, Ian Siddons; Nash, Gary (Routledge, an imprint of the Taylor & Francis Group, 2020)
"Environmental Arts Therapy: The Wild Frontiers of the Heart describes what happens when we take the creative arts therapies and the people whom we work with out of doors in order to provide safe, structured and accompanied creative therapeutic healing experiences. The theoretical themes are developed along with illustrated examples of clinical practice across a variety of settings and locations. The work is introduced and co-edited by a pioneer in the field, Ian Siddons Heginworth, who describes the emergence of environmental arts therapy and its growth across the British Isles supported through the training course based in London. The following 12 chapters are written by contributing authors and creative arts therapy practitioners working with children, adults and elders in schools, adult mental health and private practice in Britain and Europe. A central focus of the book is the clinical populations and settings in which clinicians work, and it also describes the health benefits as well as the challenges faced when working out of doors. This is a book about the emergence of a new creative therapy modality in the British Isles. It shows the value of working with the natural cycles and seasons, using an integrative arts approach including dramatic enactment, role-play, poetry, art-making with natural materials, storytelling, and the use of bodywork through movement, sound, rhythm and the voice, all held and reflected by our encounters with and in nature. It is about our relationship with nature, creativity and therapeutic healing and is written for trainers, trainees and practitioners in the creative arts, psychotherapy and ecotherapy"--Page 4 of cover.